FRI0633 Which are the ultrasound lesions underlying dactylitis?. (15th June 2017) - Toukap, A Nzeusseu; Kirchgesner, T; Lecouvet, F; Navarro, P; Berg, B Vande; Durnez, A; Stoenoiu, MS
Abstract : Background: Dactylitis, defined as a diffuse swelling of a digit is a hallmark feature of peripheral spondyloarthritis (SpA), particularly in psoriatic arthritis, with a prevalence between 16% and 48 1 . Objectives: This study aims to assess the frequency of the pathological lesions in dactylitis using ultrasonography (US) and to evaluate their association with patient-reported tenderness. Methods: Thirty-four dactylitis from 20 consecutive patients suffering from peripheral spondyloarthritis were examined by ultrasound. At US examination, the entire digit was scanned both on dorsal and palmar/plantar sides. The following US pathological lesions were scored: soft tissue thickness, soft tissue edema, soft tissue vascularization, synovitis of metacarpophalangeal (MCP)/metatarsophalangeal (MTP), of proximal interphalangeal (PIP) and of distal interphalangeal (DIP) joints, inflammatory involvement of both flexor (tenosynovitis) and extensor (paratenonitis) tendons, nail bed vascularization, synovio-entheseal complex at DIP level, enthesitis of flexor tendon, and bone proliferation. Grey-scale (GS) and power-Doppler (PD) synovitis and tenosynovitis were assessed according to OMERACT scores (0–3). Nail bed vascularization was scored 0 to 3. The other US lesions were scored 0 (absent) or 1 (present), both in GS and PD. The standard (HAQ) questionnaire, tender and swollen joint count, patient-reported tenderness, global disease activity scored by physician and by patient were assessed in all patients. Results: Twelve (60%) patients presented hand and 8 (40%) patients foot dactylitis. Twelve (60%) patients had single dactylitis. Eight patients presented with multiple dactylitis: 4 dactylitis in 1 patient, (5%), 3 dactylitis in 4 patients (20%) patients and 2 dactylitis in 3 (15%) patients. Soft tissue thickening was present in all 34 dactylitis. MCP/MTP joint synovitis was present in 28 digits (82%), PIP joint synovitis in 23 digits (68%) and DIP joint synovitis in 17 digits (50%). Extensor paratenonitis was observed in 21 digits (62%) and flexor tenosynovitis in 20 digits (59%). Enthesitis of extensor tendons was present in 21 digits (62%) and enthesitis of flexor tendon in 5 digits (15%). Osteoproliferation was present in 21 digits (62%). The frequency of synovitis, tenosynovitis and enthesitis did not differ significantly between tender (n=25) and non-tender (n=9) dactylitis. A significant association between tenderness and the presence of power Doppler (χ 2 :17.9, p<0.01) and of edema in the soft tissue was observed (χ 2 :11.5, p<0.01). Conclusions: Dactylitis is a multi-compartment digit disease, and anatomical lesions are more heterogenous than previously described. A significant amount of joint, tendon and entheseal inflammation persists in non-tender dactylitis. Patient-reported tenderness is associated with the presence of edema and/or power Doppler inside the soft tissue. References: Bakewell CJ et al. OMERACT Ultrasound Task Force. Ultrasound and magnetic resonance imaging in the evaluation of psoriatic dactylitis: status and perspectives. J Rheumatol. 2013;40:1951–7. Acknowledgements: We acknowledge S. Aydin and the OMERACT/EULAR working group for fruitful discussions. Disclosure of Interest: None declared